(untitled) (Baghdad Science Journal, 2009)
Plant regeneration and cormel production was carried out from callus cultures initiated from White Prosperity and Priscilla Gladiolus Varities. It is aimed to produce plants and cormels in vitro all year round. The study included many experiments, these were the effect of Naphthalene acetic acid (NAA) and Kinetin (Kin) interaction on callus initiation, effect of Benzyl adenine (BA) on shoot regeneration from callus culture, effect of NAA on rooting after 30, 40 and 50 days in culture. The role of the type of agricultural medium (Peat moss or river sand and their mixture on plantlets survival after weaning was studied. Results showed that the interaction between NAA and Kin induced callus on axillary bud explants. Callus was best initiated by using a combination (10.0, 0.5) mg/l for White Prosperity, (0.5, 1.0) and (10.0, 0.5) mgl for Priscilla of NAA and Kin respectively. Regeneration for the two varieties was best occurred when media were supplemented with BA at 1.0 mg/l achieving maximum number of shoots (6.2) and height (4.96 cm.). Highest response for shoot regeneration from callus occurred at a concentration of 0.5 mg/l NAA reached 100% and 83.3% for White Prosperity and Priscilla respectively. An obvious increase in rooting percentage, root number and length over time. Both varieties showed 100% response for cormels formation 50 days after rooting. Plantlets are well established in peat moss.